Fintech in Singapore: how Singapore become ASEAN leading fintech hub and the future of global fintech hub - Lim, GuoHao (2023)
During the past several years, the financial technology (Fintech) sector has grown quickly, revolutionising how individual access and manage financial services. The Fintech sector received a staggering $201 billion in investments in 2021, growing by 177% annually. Singapore has established itself as a major role in both the Asian region and the global Fintech revolution as one of the nations driving it. The nation ranks fourth overall and top in Asia for luring investments in fintech. Singapore's Fintech sector confronts several difficulties despite achievements. The country's modest market size, which might limit the possibility of further expansion, is one of the biggest obstacles.